2018
DOI: 10.1159/000489458
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Results after Internal Limiting Membrane Flap Transposition for Surgical Repair of Macular Holes with Respect to Microperimetry

Abstract: Purpose: Internal limiting membrane (ILM) flap transposition in surgical repair of macular holes represents a new technique offering good anatomical success rates with large macular holes. The aim of the study was to examine microperimetric outcomes 1 year after ILM flap transposition for surgical repair of macular holes. Methods: Patients with idi­opathic macular holes scheduled for 23-G pars plana vitrectomy with ILM peeling, ILM flap transposition, and SF6 tamponade were examined in a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The usability of microperimetry is proved in many articles, and authors put effort to find potential predictive factors for assessment of future and existing treatment [ 33 , 34 ], so it seems reasonable to perform it before vitrectomy. In a recent study of Kunikata and colleagues, microperimetry was performed preoperatively and 1, 3, and 6 months postoperatively in 21 patients with primary FTMH.…”
Section: Discussionmentioning
confidence: 99%
“…The usability of microperimetry is proved in many articles, and authors put effort to find potential predictive factors for assessment of future and existing treatment [ 33 , 34 ], so it seems reasonable to perform it before vitrectomy. In a recent study of Kunikata and colleagues, microperimetry was performed preoperatively and 1, 3, and 6 months postoperatively in 21 patients with primary FTMH.…”
Section: Discussionmentioning
confidence: 99%
“…At final follow-up period, we got the result of 100% VA improvement. It is a satisfactory outcome because Leisser et al had BCVA improved in 83% of the cases and Amram et al reported that 86% of eyes had improved BCVA at the final follow-up period of 1 year [13, 14]. Although percentage of patients with BCVA improvement is very important, it is necessary to estimate the level of final correction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] In this regard, MP can help determination of point to point retinal sensitivity and provides specific functional information of the macula and visual restoration after hole surgery. [ 21 22 23 ] Previously, several authors have demonstrated significant improvements in functional parameters measured on MP after successful MH surgery with ILM peeling. [ 19 20 24 25 26 27 28 29 30 ] After postoperative closure of the MH, the fixation status of eyes may show a complex reorganization, and fixation may become more stable with follow-up.…”
Section: Discussionmentioning
confidence: 99%